Borassus aethiopum Fruit Pulp Extract has Antimicrobial Activity on Selected Clinical Microbial Strains - Ayertey, E.; Tandoh, M. A.; Mills-Robertson, F. C.; Kumah, D. B.; Larbie, C.; Aninkorah, N. P. (Journal of Complementary and Alternative Medical Research, 2020)
This article is published in Journal of Complementary and Alternative Medical Research and also available at DOI: 10.9734/JOCAMR/2018/44495